Features of surgical treatment of esophageal injuries complicated by purulent mediastinitis - Shevchuk, I. M.; Snizhko, S. S. (Medicni Perspektivi, 2020)
The goal of the work is to improve the results of treatment of patients with esophageal perforations complicated by purulent mediastinitis. Examination and treatment of 30 patients with esophageal perforation (EP) complicated by purulent mediastinitis were performed. The causes of EP were foreign body damages in 12 (40%) of 30 patients, spontaneous rupture of the esophagus – in 11 (36.6%), iatrogenic damage to the esophagus – in 7 (23.4%) patients. The main method of surgical treatment of esophageal perforations complicated by acute purulent mediastinitis is thoracotomy with suturing of the perforated wall of the esophagus and sanation of mediastinal tissue. In case of purulent melting of the esophageal wall and total mediastinitis with severe endogenous intoxication, surgical interventions should be aimed at minimizing surgical trauma and elimination of the purulent process in the mediastinum using video-assisted thoracoscopy. The use of developed surgical tactics for the treatment of esophageal perforations complicated by acute purulent mediastinitis with intramediastinal administration of antibacterial drugs and the method of irrigation of the esophageal sutures contributes to a significant rapid reduction in endogenous intoxication, namely leukocytosis units up to 2.103±0.182 d. units (p<0,001) with normalization of the indicator on the 5th day from the beginning of treatment, the severity of the condition on the APACHE II scale in the modification of Radzikhovsky AP from 14.91±1.80 points at the time of hospitalization to 9.4±0.3 points on the second day after surgery (p<0.001), the severity of patients’ condition on the SOFA scale on the 3rd day to 3.221±0.445 points, on the 5th day – 1.832±0.219 points (p<0.001), the level of C-reactive protein on the 2nd day after surgery decreased from 236.2±21.4 mg/l to 144.3±9.3 mg/l, and on the 3rd day was 112.1±7.2 mg/l (in both cases p<0.001), reducing the content of procaltcytonin from 8.7±0.9 ng/ml to 3.828±0.251 ng/ml on the 2nd day after surgery. The use of this surgical tactic allows you to quickly eliminate the purulent process in the mediastinum, reduce the healing time of the perforation of the esophagus and reduce mortality from 28.5 to 6.2%.